Driving Success in Fast-Fashion Retail: A Moderated Mediation Model - William Widjaja; Sabil Sabil; Michael Michael; Devi Rahnjen Wijayadne (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
This study explores how work stress and participative leadership impact employee motivation in the fast-fashion industry, focusing on 130 employees in the JABOTABEK region. The research employs route analysis and moderated mediation analysis using SMARTPLS, demonstrating that job stress substantially diminishes employee motivation. However, participatory leadership exerts a favourable effect on both motivation and performance. Motivation is a vital intermediary in the correlation between job stress, participatory leadership, and employee performance. Moreover, work satisfaction is a crucial moderator influencing the correlation between motivation and performance. These findings offer theoretical insights and practical consequences for enterprises in the fast-fashion industry. They underscore the need for effective stress management strategies and highlight the importance of participative leadership and job enjoyment in enhancing employee motivation and performance, thereby contributing to improved organisational outcomes.